Soft Budget Constraints, Firm Commitments and the Social Safety Net. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1991)
It is shown that the inefficiencies created by the 'soft' budget constraint, enjoyed by enterprises in Eastern Europe and elsewhere, will continue so long as governments are unable credibly to threaten not to bail out loss-makers. Commitment to a 'hard' budget constraint can best be achieved by the institution of a suitable social safety net. The burden on the social safety net can be reduced by the (endogenous) development of financial markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet